Kajian Potensi Bakteri Lumpur Lapindo sebagai Agens Hayati terhadap Pyricularia oryzae dan Agens Biostimulan pada Tanaman Padi - ROYAN PRACAHYO; KHAMDAN KHALIMI; GEDE WIJANA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2014)
ABSTRACT The Study of Potential of Lapindo Mud Bacteria as Natural Agent Pyricularia oryzae and Biostimulant agent on Rice Rice (Oryza sativa L.) is the staple food of more than 60% of the world’s population. One of the cause for the low productivity of rice in indonesia is the occurrences of rice blast disease caused by Pycularia oryzae . This study was done to evaluate the potential use of bacteria isolated from Lapindo mud as bio-control agents against P. oryzae and bio-stimulant agents in rice plant. The result showed that three isolate of bacteria isolated from Lapindo mud namely AA1, 20M14, and ZB11 significantly (P<0,05) inhibited the growth of P. oryzae on Potato Dextrose Agar (PDA) medium with inhibitory activity varied 85,07%, 86,58%, and 70,82%. Ten isolates of bacterial isolated from Lapindo mud significantly improved the growth of rice seedling. In which the plant heigth, number of root, content of chlorophyll in the leaf, number of lateral root length of root, and the fresh and dry weight of plant significantly (P<0,05) higher on treated plant when compared to control. This is result suggested that three isolates of bacteria isolate from Lapindo mud can be further developed as bio-control agents to inhibit the P. oryzae growth and ten isolates of bacteria isolated from Lapindo mud can be used as bio-stimulan agents. Key words: lapindo mud bacteria, Pyricularia oryzae, rice